2010
DOI: 10.3389/fnhum.2010.00226
|View full text |Cite
|
Sign up to set email alerts
|

Diverting Attention Suppresses Human Amygdala Responses to Faces

Abstract: Recent neuroimaging studies disagree as to whether the processing of emotion-laden visual stimuli is dependent upon the availability of attentional resources or entirely capacity-free. Two main factors have been proposed to be responsible for the discrepancies: the differences in the perceptual attentional demands of the tasks used to divert attentional resources from emotional stimuli and the spatial location of the affective stimuli in the visual field. To date, no neuroimaging report addressed these two iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 90 publications
(153 reference statements)
2
24
0
Order By: Relevance
“…Behavioral studies show that experimental manipulation of attention reduces emotion interference produced by distractive emotional stimuli, especially when attention load to the main task is high [15, 33]. This idea gives support to the present findings, in which meditators presented the most pronounced reduction in emotional interference after training and group differences were present only in the easy condition.…”
Section: Discussionsupporting
confidence: 88%
“…Behavioral studies show that experimental manipulation of attention reduces emotion interference produced by distractive emotional stimuli, especially when attention load to the main task is high [15, 33]. This idea gives support to the present findings, in which meditators presented the most pronounced reduction in emotional interference after training and group differences were present only in the easy condition.…”
Section: Discussionsupporting
confidence: 88%
“…Please note that these are relative differences in activation, such that in the control condition, the amygdala is quite suppressed compared to baseline. The amygdala is known to undergo suppression compared to a resting baseline during an attention-demanding task (such as detecting letters in a noise pattern) (Morawetz et al, 2010; Stjepanovic et al, 2011). Thus, we interpret the less negative amygdala response to fearful face and house stimuli as a small break from the suppression of the amygdala.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that diverting attention suppresses amygdala responses to human faces [71]. The congruent activation time course of the pulvinar thalamus could be associated with a form of attention shift away from the emotionally unsettling features of the presented content.…”
Section: Discussionmentioning
confidence: 99%